KAJIAN TEOLOGI KONTEMPORER JOHN WESLEY TENTANG SPIRITUALITAS KRISTEN SEBAGAI DASAR PENGHAYATAN MENGASIHI TUHAN DAN SESAMA DI DALAM IBADAH SECARA DARING PADA MASA PANDEMI - Berty Kristina Napitupulu (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2021)
The phenomenon and reality of organizing online worship during the Covid-19 pandemic have been going on for more than a year with pros and cons at the beginning of the transition from offline to online based on the meaning of Christian spirituality. This study aims to describe Christian spirituality based on the appreciation of loving God and others in online worship during the COVID-19 pandemic. The research was conducted qualitatively through preliminary observations, online worship observations, documents, and unstructured interviews. Secondary data in the form of a literature review were analyzed exploratively. Respondents are members of the Methodist church as adherents of Wesley theology. The results of the analysis are described qualitatively based on the data obtained either through observations from online worship YouTube streaming, or from interviews with four respondents consisting of clergy, assembly members, activists, and congregations. The results show that Christian spirituality begins with the experience of being thoroughly sanctified (entire sanctification) in Christ Jesus so that the Holy Spirit who dwells within the believer will guide his spiritual life as an appreciation of love for God and others, both online and offline worship. Obstacles in organizing online worship, as well as when participating in it, can be an opportunity to deepen the love for God and others or vice versa. It was concluded that the decision to organize online worship during the pandemic itself was a form of appreciation for loving God and others, which later when the pandemic ended, online worship could be a means of evangelism as well as meeting the needs of the congregation who were in a condition where it was not possible to attend church worship.